GLOBAL STRATEGIES FOR ENVIRONMENTAL SUSTAINABILITY AND SECURITY: EDUCATIONAL IMPLICATIONS FOR YOUNG LEARNERS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article examines global scientific approaches to environmental sustainability and security and their strategic implications for primary education. Emphasizing the importance of early environmental literacy, it explores interdisciplinary curriculum design, experiential learning, and the integration of adaptive learning technologies. The study highlights how AI-based tools and real-life ecological challenges can enhance students’ environmental understanding, critical thinking, and responsible behavior. Findings suggest that embedding global sustainability principles into primary education fosters long-term ecological awareness and prepares children to make informed, environmentally responsible decisions.